THE FINANCIAL LITERATURE ANALYSIS OF SMALL MICRO ENTERPRISES AND MEDIUM IN THE KELURAHAN RAWAMANGUN JAKARTA EAST - Munada, Siti (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to analyze financial literacy can determine the resistance of MSME actors, identify the causes of MSME actors taking the decision to adopt E-Wallet as a payment aid and the causes of MSME actors taking the decision to use QRIS as a payment aid in Rawamangun sub-district Jakarta East. This study uses qualitative research methods with a phenomenological approach. Collecting data on the SMEs in the Rawamangun Village primary. Data collection uses observation, interview and documentation techniques. While the data collection technique uses triangulation techniques. The results of the analysis using the triangulation technique: (a) That financial literacy can determine the resistance of MSME activities in the Rawamangun sub-district, East Jakarta, (b) The decision of the MSMEs perpetrators in the Rawamangun sub-district, East Jakarta to adopt E-Wallet as a payment aid is a factor trust, convenience, security and speed and (c) The decision of the SMEs in the Rawamangun village, East Jakarta to use QRIS as a payment aid is that there is no clear information about QRIS.